A Proposed Islamic Multidimensional Framework of Poverty: Interviews with Global Experts - Sevinç, Nurgül; Bulut, Mehmet (Journal of Al-Tamaddun, 2023)
This study tests the proposed Islamic framework for defining poverty and its dimensions. The study has adopted a qualitative method of expert interviews to validate the proposed Islamic multidimensional poverty framework. Eight global experts on poverty were interviewed. The study’s main findings show that spirituality has priority over other biological, psychological, social, knowledge and material dimensions regarding the definition and measurement of poverty. Hence, spirituality will be the dimension shaping the remaining domains. This finding implies a policy change to reduce poverty, mainly focusing on solutions including and prioritising spirituality, which can be subjects of future research. There is no consensus on a certain list of poverty dimensions and measures. The extant conventional literature has taken a reductionist approach to poverty and less emphasised the non-material dimensions. Meanwhile, the literature on poverty from an Islamic perspective is mainly normative. In both cases, there is an absence of studies that have proposed encompassing dimensions of poverty and its measures.